Management information systems: conceptual foundations, structure, and development - Davis, Gordon B
Management information systems: conceptual foundations, structure, and development / Davis, Gordon B. -- New Delhi: Tata McGraw-Hill 658.4038 D261e2 No. of Copies : 1